1967
DOI: 10.4141/cjps67-002
|View full text |Cite
|
Sign up to set email alerts
|

Use of Protein-Based Foams to Protect Plants Against Frost

Abstract: The application of 6re-6ghting protein-based foams for use as protectire insulation of plants against frost damage is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1968
1968
1989
1989

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…English units (5). Foams developed as frost protectants and soil fumigation covers are usually more stable than those proposed for carriers in pesticide spray systems (5,8). Highstability foams typically have ER's ranging from 100 to 400.…”
Section: Foam Is Defined As Liquid Interfaces Surrounding Small Pockementioning
confidence: 99%
“…English units (5). Foams developed as frost protectants and soil fumigation covers are usually more stable than those proposed for carriers in pesticide spray systems (5,8). Highstability foams typically have ER's ranging from 100 to 400.…”
Section: Foam Is Defined As Liquid Interfaces Surrounding Small Pockementioning
confidence: 99%
“…Byrd and Seymour 6 described Vistik as a hydroxyethyl cellulose product which appears to form a visco-elastic solution in water. Suggitt 7…”
Section: Materials Added To a 2% Solution Of Ammonium Lauryl Sulfate (mentioning
confidence: 99%
“…T h e i g s a n d W r i g h t (8), S i m o n o v i t c h et al (7), a n d B r a u d et al (2) a p p l i e d foam o n plants to prevent freez ing. T h e y found that foam sprayed over plants w o u l d prevent p l a n t death by freezing, but cited the need for more stable foam mixes.…”
Section: Introductionmentioning
confidence: 99%
“…The suggestion that protein-derived fire-fighting foam might be used for the protection of plants against frost was first published in 1967 (6). The experiments that prompted this suggestion were preliminary and included only freezing tests with a few potted tomato and coleus plants totally submerged in the foam.…”
Section: Introductionmentioning
confidence: 99%
“…This foam incorporated a special formulation manufactured by Laurentian Concentrates Ltd., Ottawa, Ontario. The remarkable insulation displayed by the foam, the apparent absence of toxicity, and the spontaneous dispersal without appreciable residue led us to suggest that frost protection of plants with foam was worth further investigation (6). For practical utilization, however, the chief problem was the low stability of the foam.…”
Section: Introductionmentioning
confidence: 99%